Musaryzm: między chasydyzmem a haskalą - Postek, Halina (Studia Europaea Gnesnensia, 2014)
The aim of paper is to acquaint Polish readers with the little known religious and ethical movement which developed in the latter half of the 19th century in Lithuania. Associated with traditional Judaism, the Musar movement was to be an alternative both to Chasidism and the Haskalah